1988
DOI: 10.1016/0014-5793(88)81238-9
|View full text |Cite
|
Sign up to set email alerts
|

NMR‐invisible lactate in blood plasma

Abstract: Resonances for lactate are broadened in 500 MHz 1H NMR spectra of human blood plasma and only about one‐third is visible in Hahn spin‐echo spectra. Similar effects are observed for some other carboxylate anions. Lactate added to the high‐M r fraction of plasma can give rise to peaks which are too broad to observe in either single‐pulse or spin‐echo spectra. Addition of agents such as NH4Cl of SDS dramatically increases the intensities of lactate peaks. Some glycoproteins appear to broaden lactate resonances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 25 publications
1
62
1
Order By: Relevance
“…7) in red blood cells in the presence of DIDS. It is known that resonances of some organic anions such as lactate are often specifically broadened in the 1 H-NMR spectra of blood plasma, and the intensities of their spin±echo peaks are greatly reduced probably because of binding to proteins in human plasma [31]. Tartrate released from Sb(III)-bound form may give rise to a peak that is too broad to be observed in spin±echo spectra probably because of binding to high-molecular-mass ligands (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…7) in red blood cells in the presence of DIDS. It is known that resonances of some organic anions such as lactate are often specifically broadened in the 1 H-NMR spectra of blood plasma, and the intensities of their spin±echo peaks are greatly reduced probably because of binding to proteins in human plasma [31]. Tartrate released from Sb(III)-bound form may give rise to a peak that is too broad to be observed in spin±echo spectra probably because of binding to high-molecular-mass ligands (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of 'H NMR to quantitate lactate anion in tissue has been a point of contention recently with the conclusion that not all cellular lactate anion may be NMR visible (3). Contributions from other species resonating at similar chemical shifts (e.g., threonine) complicate the problem of quantitation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that under some conditions lactate added to the high-molecular-mass fraction of plasma gave 'H-NMR signals that were too broad to detect in either spin-echo or single-pulse spectra (Bell et al, 1988). Similarly, lactate is reported to be 40% invisible in a bovine serum albumin solution (Chatham and Forder, 1995).…”
Section: Discussionmentioning
confidence: 99%